Real Options and Risk Dynamics - Hackbarth, Dirk; Johnson, Timothy (Review of Economic Studies, 2015)
We examine the asset pricing implications of a neoclassical model of repeated investment and disinvestment. Prior research has emphasized a negative relation between productivity and equity risk that results from operating leverage when capital adjustment is costly. In general, however, expansion and contraction options affect risk in the opposite direction: they lower equity risk as profitability declines. The general prediction is a non-monotonic overlay of opposing real option and operating leverage effects. For parameters chosen to match empirical firm characteristics, the predicted non-monotonicities are quantitatively important, and are detectable in the data. The calibrated model implies that real option effects dominate operating leverage effects, and the average firm is best described by an increasing risk profile, a conclusion supported by conditional beta estimates. The baseline calibration helps explain the profitability premium in the cross-section, but makes the value puzzle worse. Panels with heterogeneous firms can deliver simultaneous profitability and value effects that match empirical levels.